Leflunomide–hydroxychloroquine combination therapy in patients with primary Sjögren's syndrome (RepurpSS-I): a placebo-controlled, double-blinded, randomised clinical trial. (May 2020) - van der Heijden, Eefje Hanna Martine; Blokland, Sofie Liny Marie; Hillen, Maarten Reinier; Lopes, Ana Paula Pinheiro; van Vliet-Moret, Fréderique Marie; Rosenberg, Antoine Johan Wilhelm Peter; Janssen, Nard Gabriëlle; Welsing, Paco Mattheus Jacobus; Iannizzotto, Valentina; Tao, Weiyang; Pandit, Aridaman; Barone, Francesca; et al.
Summary: Background: Primary Sjögren's syndrome is a systemic autoimmune disease characterised by secretory gland dysfunction, for which no effective therapy is available. Based on the complementary properties of leflunomide and hydroxychloroquine in inhibiting activation of key immune cells in primary Sjögren's syndrome, we aimed to evaluate the clinical efficacy and safety of leflunomide–hydroxychloroquine combination therapy in patients with primary Sjögren's syndrome. Methods: We did a placebo-controlled, double-blinded, phase 2A randomised clinical trial in patients with primary Sjögren's syndrome at the University Medical Center Utrecht (Utrecht, Netherlands). Eligible patients were aged 18–75 years, had a European League Against Rheumatism (EULAR) Sjögren's syndrome disease activity index (ESSDAI) score of 5 or higher, and a lymphocytic focus score of 1 or higher in labial salivary gland biopsy specimens. Patients were randomly assigned (2:1) with block randomisation (block size of six) to receive leflunomide 20 mg and hydroxychloroquine 400 mg daily or placebo for 24 weeks. The primary endpoint was the between-group difference in change in ESSDAI scores from 0 to 24 weeks, adjusted for baseline ESSDAI score. Patients were analysed according to the intention-to-treat principle. This study is registered with EudraCT, 2014–003140–12. Findings: Between March 7, 2016, and Nov 30, 2017, 37 patients were screened, of whom 29 patients (28 women and one man) were enrolled. 21 patients were assigned to receive leflunomide–hydroxychloroquine and eight patients were assigned to receive placebo. One patient in the placebo group required high-dose prednisone to treat polymyalgia rheumatica at week 13 and was excluded from the primary analysis. From 0 to 24 weeks, the mean difference in ESSDAI score, adjusted for baseline values, in the leflunomide–hydroxychloroquine group compared with the placebo group was −4·35 points (95% CI −7·45 to −1·25, p=0·0078). No serious adverse events occurred in the leflunomide–hydroxychloroquine group and two serious adverse events occurred in the placebo group (hospital admission for pancreatitis and hospital admission for nephrolithiasis). The most common adverse events in the leflunomide–hydroxychloroquine group were gastrointestinal discomfort (11 patients [52%] vs two [25%] in the placebo group), modest transient increases in alanine aminotransferase (ten [48%] vs one [13%]), and short episodes of general malaise and shivering (nine [43%] vs one [13%]). Interpretation: Leflunomide–hydroxychloroquine was safe and resulted in a clinical response in patients with primary Sjögren's syndrome. These results warrant further evaluation of leflunomide–hydroxychloroquine combination therapy in larger clinical trials. Funding: ZonMw.